Review : Pendekatan Metabolomik Untuk Authentifikasi Kehalalan Daging Berdasarkan Cara Penyembelihannya - Maritha, Vevi; Kartini, Puri Ratna; Basy, Lukman La (Universitas PGRI Madiun, 2023)
Halal meat is a concern in many countries, including Indonesia. This is because halal meat can not only be accepted by Muslims but also by non-Muslims. The process of slaughtering meat is one of the critical points to authenticate the halalness of meat. Halal meat that is slaughtered not according to sharia will make meat that should be halal become non-halal. Therefore, a method is needed that is able to authenticate the halalness of meat based on the slaughter process, through a metabolomics approach. Metabolites are the result of gene expression with the environment so that the metabolites of meat slaughtered not according to sharia will be different from metabolites that are slaughtered according to sharia. To facilitate visualization of halal authentication, chemometric analysis is needed. Chemometrics will reduce a lot of metabolite data to be simpler so that it is easier to understand. The metabolomics approach combined with chemometrics will be an alternative method that can be used to authenticate the halalness of meat based on the slaughter process.